Pengaruh Gaya Kepemimpinan dan Komunikasi terhadap Kinerja Karyawan PT IPC Terminal Petikemas di Pelindo Tower - Fasya, Lathan Abdillah; Pratomo, Triaji Prio (eProceedings of Management, 2025)
PT IPC Terminal Petikemas plays an important role in supporting logistics and port activities. However, the company’soperational effectiveness has not yet been fully optimized. Leadership style and communication are considered to have aninfluence on employee performance, which is one of the key factors affecting overall performance. The purpose of thisstudy is to determine how these two factors influence workplace productivity at Pelindo Tower. This quantitative descriptiveresearch aims to describe the relationship between leadership style, communication, and employee performance usingempirical data. The population in this study consisted of 134 employees of PT IPC Terminal Petikemas, with a sample of100 employees selected through purposive sampling. Data collected through questionnaires were analyzed using multiplelinear regression with SPSS. The findings indicate a strong interaction between leadership style and communication, whichin turn affects employee performance. Based on hypothesis testing, both leadership style and communication, eitherpartially or simultaneously, have a significant effect on employee performance. According to the coefficient ofdetermination, these two independent variables leadership style and communication explain 78.6% of the variance in thedependent variable, namely employee performance.Kata Kunci: Leadership Style, Communication, Employee Performance